ANALYSIS OF THE EFFECT OF PRODUCT KNOWLEDGE, BANK REPUTATION, AND BANKING DIGITALIZATION ON SAVING DECISIONS IN SHARIA COMMERCIAL BANK (STUDY ON THE PEOPLE OF SEMARANG CITY) - Salma Rohadatul Aisy; Nyata Nugraha; Sri Hardiningsih (Politeknik Negeri Semarang, 2022)
This study aims to analyze the significance of the effect of Product Knowledge, Bank Reputation, and Banking Digitalization on Saving Decisions in Sharia Commercial Bank on the people of Semarang City both simultaneously and partially. The population in this study was all people in Semarang City, Central Java, while the sample in this study was 75 respondents selected using purposive sampling techniques. The data used in this study are primary data obtained through questionnaires. The analysis model used in this study is multiple linear regression analysis, while the analysis technique uses the F statistic test, coefficient of determination test (R2), and t statistic test with the SPSS 26 computer program. The results of hypothesis testing and discussion show that Product Knowledge, Bank Reputation, and Banking Digitalization have a significant effect on Saving Decisions both simultaneously and partially.